Effectiveness of flood early warning for the Jamuna char-dwellers at Sirajganj District in Bangladesh - Md. Mehedi Hasan; Mohammad Najmul Islam (Progress in Disaster Science)
Floods, a pervasive global natural disaster, are a recurrent challenge in Bangladesh, causing substantial damage to property, infrastructure, and lives. The country has implemented a flood warning system since 1972, focusing on people, property, and cost-effectiveness. However, the efficacy of this system relies on accurate and timely dissemination of warnings and prompt responses from at-risk communities to mitigate losses and damages. This study evaluates the effectiveness of the flood early warning systems at the grassroots level in Sirajganj District, specifically in two purposively selected villages within the Kaijuri Union. One village is situated along the unprotected bankline, while the other is in the island char area. Data was gathered from 116 households through interviews, focus group discussions, and key informant interviews. Results of the Multi-criteria analysis reveal that the system is moderately effective for the bankline village (Kaijuri) with a score of 0.400, but considerably less effective for the char-land village (Thutia) with a score of 0.174. Inadequate communication links contribute to delayed and unreliable information, leading to higher losses and damages. The study emphasizes the necessity of building community trust by involving them in the planning and management of flood warning systems for more effective risk reduction.